2011
DOI: 10.1007/s10711-011-9623-y
|View full text |Cite
|
Sign up to set email alerts
|

The Dehn function of Baumslag’s metabelian group

Abstract: Baumslag's group is a finitely presented metabelian group with a Z Z subgroup. There is an analogue with an additional torsion relation in which this subgroup becomes C m Z. We prove that Baumslag's group has an exponential Dehn function. This contrasts with the torsion analogues which have quadratic Dehn functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 24 publications
0
14
0
4
Order By: Relevance
“…Several of the techniques developed to deal with RAAGs have applications in other groups. "Pushing" may be used in the torsion analogs of Baumslag's metabelian group to find that the Dehn function is at worst quartic, as shown in [25]-a priori, it takes nontrivial work even to show that the Dehn function is polynomial. (In fact, it turns out to be quadratic, as shown by de Cornulier-Tessera in [10].)…”
Section: Introductionmentioning
confidence: 99%
“…Several of the techniques developed to deal with RAAGs have applications in other groups. "Pushing" may be used in the torsion analogs of Baumslag's metabelian group to find that the Dehn function is at worst quartic, as shown in [25]-a priori, it takes nontrivial work even to show that the Dehn function is polynomial. (In fact, it turns out to be quadratic, as shown by de Cornulier-Tessera in [10].)…”
Section: Introductionmentioning
confidence: 99%
“…De Cornulier & Tessera showed that the Dehn function of Γ 2 (2) grows quadratically [18], and Kassabov & Riley [30] that that of Γ 2 grows exponentially.…”
Section: Cayley Graphs Of Generalized Lamplighter Groupsmentioning
confidence: 99%
“…It was shown in [3] that when p is prime, Γ 3 (p) is a cocompact lattice in Sol 5 (F p ((t))), and its Dehn function is quadratic. The Dehn function of Γ 3 (m) is studied for any m in [12] where it is shown to be at most quartic.…”
Section: Introductionmentioning
confidence: 99%